Amphipoda (Crustacea) from Palau, Micronesia: Families Dexaminidae, Eusiridae, Hyalidae, Ischyroceridae, Leucothoidae and Lysianassidae - Myers, A. A. (Zootaxa, 2013)
Thirteen species of amphipod in the families Dexaminidae (1), Eusiridae (1), Hyalidae (1), Ischyroceridae (1), Leucothoidae (8) and Lysianassidae (1) are recorded from Palau in Micronesia. Of these, Ventojassa palauensis sp. nov., Leucothoe beobeldabensis sp.nov., L. pseudepidemos sp. nov., L. serratissima sp. nov., L. tumida sp. nov., L. whiteae sp. nov and Paranamixis dentidactylus sp. nov. are new to science and are described and figured.